REAKSI ESTERIFIKASI ?-PINENA MENJADI ?-TERPENIL ASETAT DENGAN KATALIS ZEOLIT ALAM - Wijayati, Nanik; Purwodiningsih, Ristia; Widarti, Nuni; Kusumastuti, Ella (Sainteknol : Jurnal Sains dan Teknologi, 2017)
Turpentine is one of the oil obtained from pine tree with composition of 82% ?- pinene. Turpentin oil has a high sales value is to make the esterification reaction ?-pinene to get ?-terpinyl.   Usually esterification ?-pinene is carried out with homogeneous catalysts are corrosive and unreusable.   The purpose of the research  are to know the optimum reaction time(2, 3, 4 jam), optimum reaction temperature (30, 40, 60ºC)and optimum mol ratio of reactants (1:5, 1:15, 1:20) between ?-pinene and acetic anhydride for esterification ?-pinene to ?-terpinyl acetate using natural zeolite. Characterization of catalyst involve X- ray   Diffraction,   spectroscopy   IR   and   Scanning   Electron   Microscopy.   Product   of esterification reaction analyzed using spectroscopy IR, gas chromatography, and gas chromatography-mass  spectroscopy.  Result  of  the  analysis  using  spectrocopy  IR  show absorption of C-H at 2923 cm-1, C=O at 1725 cm-1, C=C at 1617 cm-1 and C-O at 1254 cm-1. The reaction time effect the conversion of ?-pinena  while reaction temperature and mol ratio of reactants effect on the increased levels of reaction products produced.  The optimum conditions for esterification reaction ?-pinene to ?-terpinyl acetate is at temperature of 40ºC  during 3 hours with mol ratio of reactants between ?-pinene and acetic anhydride is 1:15 to produce ?-terpenyl acetate amewweounted to 21,40%. Keywords: ?-pinena, esterification, ?-terpinyl acetate